Cystic Fibrosis Papers of the Year, 2013-2014. (October 2015) - Simmonds, Nicholas J.
Summary: Studies published in the last year in the field of cystic fibrosis have provided more data on the safety and efficacy of a number of therapies, including mutation-specific drugs. There have also been a number of publications on monitoring of early lung disease including the use of lung clearance index and magnetic resonance scanning. Evidence suggests early lung changes may remain relatively static over the first year of life. There are important outcome differences across national patient registries and there is also the increasing recognition of psychological illnesses and possible drug interactions as treatment becomes more complicated and survival improves.